THE RADICAL FEMINISM OF IMPERATOR FURIOSA’S CHARACTER IN MAD MAX FURY ROAD FILM (2015) - Sibarani, Soraya Prasasty Marito; Natsir, M.; M., Fatimah (Fakultas Ilmu Budaya Universitas Mulawarman, 2020)
The purposes of this research were to find out the way of Imperator Furiosa’s character represents in radical feminism in Mad Max Fury Road film (2015). The design of this research was qualitative research. The data of this research were taken from dialogue, scene, action, and speech based on the film. The data of this research were analyzed by using radical feminism theory by Rosemarie. P. Tong in Feminist Thought a More Comprehensive Introduction (2009) and the categorized as Furiosa’s character representation of radical feminism through the theory of indirect characterization by Kelly Griffth. The result of this research showed Imperator Furiosa represented two kinds of radical feminism. First was radical libertarian feminism which were androgyny which found in the Furiosa’s character appearance, character dialogue, character speech, character action. And seizes the meaning of reproduction which found in the Furiosa’s character dialogue. Second was radical cultural feminism which is women using reproduction as a trump card and power which found in the Furiosa’s character speech.